Evaluation of Soil Samples in Abeokuta-South Local Government Area of Ogun State, Southwestern Nigeria - Bello, A. A.; Oriaje, A. T. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
This paper presents result of a laboratory investigation on soil samples from Abeokuta South Local Government, Southwestern Nigeria. Three comparative efforts namely standard Proctor (SP), West African Standard (WAS) and modified Proctor (MP), were employed. The results obtained showed that the compaction characteristics and unconfined compressive strength of the soil samples were found to increase with comparative effort. The unconfined compressive strength (UCS) values increased with compactive effort and decreased with increase in degree of saturation of the soil samples. All the samples did not meet the minimum specified requirements except for A1, A6 and A8. Upon stabilized with cement, samples A2 and A7 did not also meet the minimum CBR value of 180% as specified by the Nigerian General Specification for roads and bridgeworks (1997) or stabilized soil using standard Proctor compactive effort at 4% cement content. However, all the soil samples met the requirement using WAS compactive effort at 4% cement content. The samples met the conventional UCS values of (1500-3000 kN/m2) for base course of lightly trafficked roads while only sample A4 compacted at 10% cement content using WAS compactive effort met the minimum (3000- 6000 kN/m2) for base course of highly trafficked road. It is thus recommended that 4% cement should be used as an optimal content to stabilize the soils, if they are to be used as road construction materials.